Spirochetes isolated from arthropods constitute a novel genus Entomospira genus novum within the order Spirochaetales - Graña-Miraglia, Lucía; Sikutova, Silvie; Vancová, Marie; Bílý, Tomáš; Fingerle, Volker; Sing, Andreas; Castillo-Ramírez, Santiago; Margos, Gabriele; Rudolf, Ivo (Scientific reports, 2020)
Spirochetal bacteria were successfully isolated from mosquitoes (Culex pipiens, Aedes cinereus) in the Czech Republic between 1999 and 2002. Preliminary 16S rRNA phylogenetic sequence analysis showed that these strains differed significantly from other spirochetal genera within the family Spirochaetaceae and suggested a novel bacterial genus in this family. To obtain more comprehensive genomic information of these isolates, we used Illumina MiSeq and Oxford Nanopore technologies to sequence four genomes of these spirochetes (BR151, BR149, BR193, BR208). The overall size of the genomes varied between 1.68 and 1.78 Mb; the GC content ranged from 38.5 to 45.8%. Draft genomes were compared to 36 publicly available genomes encompassing eight genera from the class Spirochaetes. A phylogeny generated from orthologous genes across all taxa and the percentage of conserved proteins (POCP) confirmed the genus status of these novel spirochetes. The genus Entomospira gen. nov. is proposed with BR151 selected as type species of the genus. For this isolate and the closest related isolate, BR149, we propose the species name Entomospira culicis sp. nov. The two other isolates BR208 and BR193 are named Entomospira nematocera sp. nov. (BR208) and Entomospira entomophilus sp. nov. (BR193). Finally, we discuss their interesting phylogenetic positioning.
Keywords: zastoupení bazí; Base Composition; Sequence Analysis, DNA; Spirochaetales; Phylogeny; RNA ribozomální 16S; sekvenční analýza DNA; Arthropods; Bacterial Typing Techniques; DNA, Bacterial; DNA bakterií; Animals; členovci; Spirochaeta; zvířata; fylogeneze; techniky typizace bakterií; RNA, Ribosomal, 16S